2020
DOI: 10.1080/03071847.2020.1736437
|View full text |Cite
|
Sign up to set email alerts
|

Proxy Warfare and the Future of Conflict: Take Two

Abstract: 4contemporary civil wars into complex proxy wars in strategic settings ranging from South-East Ukraine 6 and central Africa 7 to the porous borders of Syria 8 and Yemen. 9In 2013, the RUSI Journal published Andrew Mumford's discussion on the role of proxy warfare in shaping future conflict 10 as a preamble to his wider analysis of the phenomenon. 11 Taken together, Mumford's work revived a debate long ignored by strategic and security studies. Fast forward six years and the future of proxy wars has become thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Examples of the materialization of this model are: the support given by the US to Iraq for the defeat of ISIS, the support provided by Russia to Syria in the framework of the civil war, etc. Regardless of the model in which proxy warfare fits, it will remain a preferred form of conducting conflicts, repositioning spheres of influence or releasing tensions on the international stage and will remain "a core feature of the contemporary and future strategic and security environment" [9], because, in theory, proxy war is a simple solution to a complex problem. In practice, however, it has been found that proxy war is actually a simple solution only in the short term, because the evolution of events is unpredictable and most of the time the consequences and effects are not anticipated and are very difficult to manage.…”
Section: Main Models Of the Agent-sponsor Relationship In Modern Prox...mentioning
confidence: 99%
“…Examples of the materialization of this model are: the support given by the US to Iraq for the defeat of ISIS, the support provided by Russia to Syria in the framework of the civil war, etc. Regardless of the model in which proxy warfare fits, it will remain a preferred form of conducting conflicts, repositioning spheres of influence or releasing tensions on the international stage and will remain "a core feature of the contemporary and future strategic and security environment" [9], because, in theory, proxy war is a simple solution to a complex problem. In practice, however, it has been found that proxy war is actually a simple solution only in the short term, because the evolution of events is unpredictable and most of the time the consequences and effects are not anticipated and are very difficult to manage.…”
Section: Main Models Of the Agent-sponsor Relationship In Modern Prox...mentioning
confidence: 99%
“…In this context, it is relevant to understand proxy war as "a violent armed interaction resulting from the polarisation of competing political goals" between two rivals in which at least one engages the other indirectly through a third party, the proxy (Rauta, 2018, p. 467). Moreover, policymakers should think about assessing how different actors might employ proxies (Moghadam & Wyss, 2020;Rauta, 2020b), as well as the existence of different proxy logics or modalities (Fox, 2020), by considering insights derived from understanding proxy wars both as a global problem, but also one with decisively specific regional characteristics (Rauta, 2021a).…”
Section: Keeping It Simple: Hybrid Threats and Hybrid Warfarementioning
confidence: 99%
“…The reformers' scholarship has expanded exponentially across special issues, think tank reports (Rondeaux & Sterman, 2019), monographs (Groh, 2019;Jones, 2017), and roundtable discussions (Wirtz et al, 2020). More importantly, it has linked proxy wars to a wide range of security issues, and provided more robust discussion of some core problems: provision of support and control of proxies (Moghadam & Wyss, 2020;Rauta, 2020), and moral/ethical dilemmas of supporting proxies (Pfaff, 2017;Pattison, 2018). No wonder that this expansion had conflict research ask the question of "how might we incorporate the idea of proxy war in the study of civil war to broaden the general understanding of how civil wars occur and end?"…”
Section: Reformersmentioning
confidence: 99%
“…Strategy and strategic interaction provide a theoretical framework to assess complexity in a way that provides meaning to the sets of political violence meeting on the battlespace: of the delegating state or non-state actor, of the proxy, of the intermediary facilitating the provision of support between sponsor and proxy, as well as of the target and their sponsors, if any (Rauta, 2020). This is perhaps even more relevant given that when we identify a proxy war we often identify a complex of inter-locked proxy wars.…”
Section: Strategy and Proxy War Researchmentioning
confidence: 99%